Rhetorical Authority and Knowledge Construction in EFL Doctoral Dissertation Abstracts - Yulhenli Thabran (Universitas Cokroaminoto Palopo, 2026)
Doctoral dissertation abstracts function not only as summaries of research but also as rhetorical spaces where doctoral writers construct scholarly authority and position knowledge within disciplinary communities. Despite growing research on academic genres and metadiscourse, limited attention has been given to the relationship among rhetorical organization, interpersonal positioning, and epistemic orientation in doctoral dissertation abstracts, particularly in non-Anglophone EFL contexts. This qualitative discourse-analytic study examines 18 PhD dissertation abstracts produced between 2021 and 2025 in an English Education doctoral program at a public university in Indonesia. Drawing on genre analysis, interpersonal metadiscourse theory, and epistemic perspectives on academic writing, the study investigates how doctoral writers organize abstracts, construct rhetorical authority, and represent knowledge. The findings show that the abstracts strongly emphasize research purpose, methodology, and results, while background framing and contribution-oriented closure are less consistently developed. Interactional metadiscourse features, including hedging, evaluative language, and reader engagement, are used infrequently, resulting in rhetorical authority being constructed mainly through procedural clarity and confident reporting. Most abstracts also display a knowledge-telling orientation characterized by linear presentation and limited interpretive synthesis. The study demonstrates that genre organization, interpersonal positioning, and epistemic orientation interact closely in shaping doctoral abstract writing. These findings contribute to research on doctoral literacy and academic discourse and suggest the importance of explicitly teaching contribution framing, stance-taking, and rhetorical positioning in doctoral writing pedagogy.